Invasão biológica por Ligustrum lucidum W. T. Aiton no Parque Estadual Quarta Colônia, RS - Hummel, Rafaela Badinelli (2015)
The objective of this study was evaluate the process of biological invasion by Ligustrum lucidum in the Quarta Colônia State Park (QCSP), central region of Rio Grande do Sul, Brazil, tried to understand how this species established itself inside of the conservation unit (CU), and the population perception over L. lucidum by the execution of interviews with local residents close to the park, and by mapping the individuals found nearby. Trying to understand the dynamic of the species during the restoration phase in a remaining of Deciduous Forest located inside the PA, we performed floristic surveys among 2011, 2013 and 2014, evaluated through phytosociological parameters, diameter distribution, space distribution, biological invasion indicator, and the relation between the species and environmental factors. The results of the interviews showed that L. lucidum was purposely used inside and outside the CU with ornamental intents. Most of participants unknown the species by its name, not even the people who have it on their residences, which demonstrates low affinity with the species and strengths the presupposition that it was only used in high frequency due to the trends of arborization in the last decades. It was found 31 individuals of this species in the farms nearby the QCSP. L. lucidum presented strong correlation with the content of clay, calcium and cation exchange capacity however the opposite correlation was founded with phosphorus, magnesium and organic matter. The adult stratum presented generalist character, without significative correlation with the evaluated physical-chemistry characteristics. In the interval classes considered in the regeneration, the species presented an opportunist character regarding the sorptive matrice, related to the contribution of clay to the changeable sites, occupied specially by calcium. Regarding the dynamic in the remaining forest studied, L. lucidum can be considered a menace to the native species, since its density and frequency are increasing, mainly in the regenerating stratum, which guarantees the permanence of the L. lucidum at the site, and menacing biodiversity. The ecosystem structure of the remaining forest in restoration may be harmed by the presence of this species, and this situation may become more severe if the adequate measures of control would not be taken, involving not only the elimination of individuals inside the CU, but also an environmental educational work inserting the population living nearby the QCSP with awareness actions and control the use of invasive species in the farms. The L. lucidum show high invader potential in the studied area, and the mainly features are opportunist character during regeneration phase.